2011
DOI: 10.1002/jwmg.149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of black bear relocation on elk calf recruitment at Great Smoky Mountains National Park

Abstract: Previous research from 2001 to 2006 on an experimentally released elk (Cervus elaphus) population at Great Smoky Mountains National Park (GSMNP or Park) indicated that calf recruitment (i.e., calves reaching 1 yr of age per adult female elk) was low (0.306, total SE = 0.090) resulting in low or negative population growth (λ = 0.996, 95% CI = 0.945–1.047). Black bear (Ursus americanus) predation was the primary calf mortality factor. From 2006 to 2008, we trapped and relocated 49 bears (30 of which were radioco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…, l = process variance for estimate reported in Yarkovitch et al. , m = mean not weighted by sample size because sample size not reported for some studies, n = vital rate not included in weighted mean calculation.…”
Section: Methodsmentioning
confidence: 99%
“…, l = process variance for estimate reported in Yarkovitch et al. , m = mean not weighted by sample size because sample size not reported for some studies, n = vital rate not included in weighted mean calculation.…”
Section: Methodsmentioning
confidence: 99%
“…Predation: The Wapiti that were originally released into the Park had never dealt with American Black Bears as predators and, as a result, during the early years of the Wapiti reintroduction, calf survival was low (Yarkovich 2009). Black Bears were relocated during calving season as a method to reduce predation on the Wapiti calves (Yarkovich 2009).…”
Section: Family Cervidae -Deermentioning
confidence: 98%
“…Black Bears were relocated during calving season as a method to reduce predation on the Wapiti calves (Yarkovich 2009). Survival rates for calves has increased over the years (Yarkovich 2009), so it seems that over time, the Wapiti have learned to deal with bears and to hide and defend their newborns against them. Coyotes also prey on Wapiti calves (Yarkovich 2009).…”
Section: Family Cervidae -Deermentioning
confidence: 99%
“…Ozoga and Verme (1982) concluded that a significant loss of fawns to black bears may be possible, although their study was limited to an enclosure. Researchers have also found evidence that black bears may negatively affect recruitment of calves in a reintroduced population of elk in the eastern U.S. (Yarkovich et al 2011), but research has also suggested that predation appears to have a larger affect at lower ungulate densities (Zagar and Beechum 2006). In Idaho, elk calf survival seemed to be influenced by birth weight, habitat structure, and black bear and cougar harvest (presumably in relation to their respective densities); calf mortality through predation by black bears was described as additive (i.e., in addition to, rather than replacing, other sources), and the authors suggested that a spring bear season may be effective for improving calf survival (White et al 2010).…”
Section: Foraging and Predationmentioning
confidence: 99%